On-chip broadband laser source using chalcogenide glass planar waveguide - غزال, فريد; شقة, يوسف; مباركي, سفيان (university of Eloued جامعة الوادي, 2019)
The work presented in this manuscript concerns the study and modeling of the linear and non-linear properties of optical waveguide (ridge waveguide), and this for create a Broadband laser source on an optical chip using a chalcogenide glass waveguide As2S5. The linear and nonlinear optical properties have been calculated and optimized by using a fully vectorial finite-difference in the frequency-domain (FDFD) method. The results of simulations show that with a good optimization of the waveguide structure, to exhibit an all normal dispersion (ANDi) profile over the entire computational domain and this by properly adjusting its high and width, we've got a broad and perfectly coherent ultra-flat SC spectrum extending from 700 to 5300 nm, and this is also by exploiting the nonlinear effects that appear in waveguide during the propagation of ultra-short pulses (femtosecond). The physical model and the contribution of different nonlinear effects are presented in numerical modeling, on the other hand, is based on the solution of the generalized nonlinear Schrödinger equation (GNLSE). يتعلق العمل المقدم في هذه الاطروحة بدراسة ونمذجة الخصائص الخطية وغير الخطية لموجه الموجة الضوئية (موجه موجة ريدج) ، وهذا لإنشاء مصدر ليزر واسع النطاق على رقاقة بصرية باستخدام زجاج As2S5 . تم حساب الخصائص البصرية الخطية وغير الخطية وتحسينها باستخدام طريقة (FDFD). تظهر نتائج عمليات المحاكاة أنه مع التحسين الجيد لهيكل موجه الموجه بما يضمن تبدد طيفي سالب من أجل كل أطوال الأمواج (ANDi) وهذا عن طريق ضبط ارتفاعه وعرضه بشكل صحيح ، أصبح لدينا نطاق طيفي SC فائق ومتسق تمامًا و مسطح يمتد من 700 إلى 5300 نانومتر ، وهذا أيضًا عن طريق استغلال التأثيرات غير الخطية التي تظهر في موجه الموجي أثناء انتشار نبضات قصيرة للغاية (فيمتوثانية). يتم تقديم النموذج المادي ومساهمة التأثيرات غير الخطية المختلفة في النمذجة العددية ، وذلك باعتماده على حل معادلة شرودنجر غير الخطية العامة (GNLSE) .
مذكرة ماستر تخصص في انظمة الاتصالات
Keywords: Optical waveguide, Chromatic dispersion, Supercontinuum generation, Nonlinear optics.; موجه موجي بصري، تبدد طيفي، طيف واسع مستمر، بصريات لاخطية.